Performance study of solar photovoltaic cold storage system using phase change materials. (2021) - Sarafoji, P.; Mariappan, V.; Anish, R.; Karthikeyan, K.; Reddy, Jayabharata
Abstract: Phase change material technology has great potential in energy storage and cost-saving in the applications of cold thermal energy storage. This study presents the performance and evaluation of phase change material (PCM) in the Prototype Solar Cold Storage (PSCS) system. Five different experiments were conducted to measure the performance of the PSCS system. The experiment results showed that 16 kg of PCM charged in 75–90 min and able to maintain the temperature within the setpoint about an average of 150 min. However, PCM is a promising material for cold thermal energy storage applications. Also, Solar Photovoltaic (PV) integrated with the cold storage system and the tested results indicate the grid energy replaced by solar and PCM about 16% of the total power consumption. Besides, the proposed technologies are suitable for solar PV generation & reduction of greenhouse gas emissions.